Energy Intake, Macro Nutrition and Nutritional Status of Preeclampsia Patients in The RSIA Siti Fatimah, Makassar - Andi Syam Haeru; Wibowo Wibowo (Humanistic Network for Science and Technology (HNST), 2019)
Preeclampsia until now is still a health problem that can not be solved completely. Statistical data in developed countries show that 10-30% of all maternal deaths are caused by preeclampsia. Preeclampsia is one of the three major causes of maternal death in addition to bleeding and infection. Nutritional intake is an indicator to see the nutritional adequacy and upper arm circumference of pregnant women is one tool to assess the nutritional status, so it can be known complications during pregnancy. This study aims to determine how the relationship of energy intake and macro nutrition and nutritional status with the incidence of preeclampsia in the RSIA Siti Fatimah Makassar. The type of this research was a cross-sectional study. Data collection was done by interview using a questionnaire with sample size of 34 people. The result of the research using statistical analysis of Chi-square test showed that energy intake, protein intake, fat intake, and carbohydrate intake as well as nutritional status were obtained by p-values of 0.584, 0.611, 0.416, 0.649 and 0.547 means that there was no relationship between energy intake and macro nutrition and nutritional status in patients preeclampsia in the RSIA Siti Fatimah Makassar. It is expected that the respondent health officer can increase the frequency of counseling both personally and group-related factors that can influence the occurrence of preeclampsia. Keywords: Intake of energy, Macronutrient, Nutritional status, Preeclampsia